TINJAUAN TEORI HUKUM EKONOMI PADA PERJANJIAN SEWA BARANG MILIK NEGARA (Studi Kasus Kantor Unit Penyelenggara Pelabuhan Kelas III Kuala Samboja Direktorat Jenderal Perhubungan Laut dengan PT. Tanjung Berlian Samboja) - Febrina Indrasari (Universitas Muhammadiyah Ponorogo, 2023)
The purpose of this study is to determine the lease agreement of State Property (BMN) in terms of economic law theory. The research method uses a Doctrinal approach which is normative in character with research targets from a set of norms, at the application level, or research depth. Current infrastructure development requires efficiency, effectiveness of state spending and increased state revenue. In practice, Non-Tax State Revenue (PNBP) as state revenue has not been implemented optimally by the Ministry of State / Department. One of them is PNBP derived from the management of State assets, namely State Property (BMN). Alternative utilization of BMN by leasing BMN implemented by Ministries / Institutions in the scope of East Kalimantan, namely the utilization of BMN located at the Kuala Samboja Class III Port Operator Unit Office, the asset is leased for the stockpiling of land construction goods at Ambarawang Laut Port. So the researcher wants to know how the BMN utilization lease agreement from the Economic Analysis of Law theory, Investment theory, and how the BMN utilization Lease Agreement at the Kuala Samboja Class III Port Operator Unit Office in terms of agreement law. The results: (1) The BMN utilization lease agreement from the Economic Analysis of Law theory sees the role of law in terms of value, usefulness, and efficiency can be applied; (2) The contract signing process takes a long time, because on the leasing side there are several agencies in the approval, such as the Ministry of Finance and the Ministry of Transportation internally; (3) BMN utilization is seen by investment theory to be very beneficial for both parties; (4) BMN utilization lease agreement seen from the elements of the agreement, legally valid.